Assessment of Site Development Compliance with GBC Indonesia Greenship Criteria in a Technology Office Complex - Cahyo Riyadi, Irfan; Ahmad Husin, Nur; Rahardjo, Budi (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
The increasing demand for land in urban development highlights the urgent need for sustainable construction practices. While green building concepts have gained global traction, the application of appropriate site development remains understudied in the Indonesian context. This study evaluates the implementation of the Appropriate Site Development (ASD) category based on the Greenship New Building v1.2 rating tool developed by the Green Building Council Indonesia (GBCI), using the Techno Building at the BRI IT Center in Jakarta as a case study. A descriptive-evaluative method was applied to assess compliance across seven criteria within the ASD category. Initial findings revealed a score of 12 out of 17 possible points, with deficiencies identified in public transportation (1/2 points), bicycle facilities (0/2), and microclimate (1/3). After proposing improvements, such as shuttle services, bicycle parking, and the use of high-albedo materials, the building achieved full compliance with 17/17 points. These results indicate that although external constraints exist (e.g., regulatory and geographic limitations), internal strategies can substantially improve green building certification outcomes. The study highlights the critical role of early site planning and internal design adjustments in achieving sustainability benchmarks.